2009
DOI: 10.1007/s00401-009-0625-x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of peptidylarginine deiminase-mediated post-translational citrullination in pathogenesis of sporadic Creutzfeldt-Jakob disease

Abstract: Peptidylarginine deiminases (PADs)-mediated post-translational citrullination processes play key roles in protein functions and structural stability through the conversion of arginine to citrulline in the presence of excessive calcium concentrations. In brain, PAD2 is abundantly expressed and can be involved in citrullination in disease. Recently, we have reported pathological characterization of PAD2 and citrullinated proteins in scrapie-infected mice, but the implication of protein citrullination in the path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 65 publications
5
36
0
1
Order By: Relevance
“…Recent studies have demonstrated that accumulated citrullinated proteins and abnormal activation of peptidylarginine deiminase 2 (PAD2) may play a role in the pathogenesis of prion diseases. 4,5 In addition, citrullinated proteins including glial fibrillary acidic protein (GFAP), myelin basic protein (MBP), and several newly identified proteins were found in prion disease and other neurodegenerative diseases. [4][5][6] PADs and citrullination.…”
Section: Peptidylarginine Deiminase and Protein Citrullination In Primentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have demonstrated that accumulated citrullinated proteins and abnormal activation of peptidylarginine deiminase 2 (PAD2) may play a role in the pathogenesis of prion diseases. 4,5 In addition, citrullinated proteins including glial fibrillary acidic protein (GFAP), myelin basic protein (MBP), and several newly identified proteins were found in prion disease and other neurodegenerative diseases. [4][5][6] PADs and citrullination.…”
Section: Peptidylarginine Deiminase and Protein Citrullination In Primentioning
confidence: 99%
“…4,5 In addition, citrullinated proteins including glial fibrillary acidic protein (GFAP), myelin basic protein (MBP), and several newly identified proteins were found in prion disease and other neurodegenerative diseases. [4][5][6] PADs and citrullination. The post-translational citrullination process is defined as the modification of an arginine residue to a citrulline residue in proteins, and this process is mediated by calcium (Ca 2+ )-dependent PAD enzymes (Fig.…”
Section: Peptidylarginine Deiminase and Protein Citrullination In Primentioning
confidence: 99%
See 2 more Smart Citations
“…L'augmentation du taux de protéines citrullinées et la surexpression de Pad2 dans le cerveau de souris infectées par la protéine scrapie (souche ME7) tendent à prouver l'implication de cet isotype dans les maladies neurodégénératives à prions [16]. Tout récemment, une expression accrue de PAD2 et une augmentation de la désimination ont effectivement été démontrées chez l'homme dans des cas sporadiques de la maladie de Creutzfeldt-Jakob [17]. PAD2 et des taux anormalement élevés de désimination ont également été observés au niveau du nerf optique dans des cas de glaucome ou dans les cellules épithéliales des capsules de Bowman du rein lors du développement d'une néphropathie expérimentale (pour revue voir [6]).…”
Section: Implication De La Désimination Et Des Pad Dans De Nombreusesunclassified